2021
DOI: 10.3390/molecules26227005
|View full text |Cite
|
Sign up to set email alerts
|

Review of Nephelium lappaceum and Nephelium ramboutan-ake: A High Potential Supplement

Abstract: Nephelium lappaceum (N. lappaceum) and Nephelium ramboutan-ake (N. ramboutan-ake) are tropical fruits that gain popularity worldwide due to their tastiness. Currently, their potential to be used as pharmaceutical agents is underestimated. Chronic diseases such as cancer, diabetes and aging have high incidence rates in the modern world. Furthermore, pharmaceutical agents targeting pathogenic microorganisms have been hampered by the growing of antimicrobial resistance threats. The idea of food therapy leads to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
2
0
2
Order By: Relevance
“…No que diz respeito à atividade antioxidante de N. lappaceum, verificou-se que a respetiva casca tem maior poder antioxidante, em comparação com a semente e a folha, devido ao seu teor de flavonoides e compostos fenólicos, como a geraniina (25).…”
Section: Dos Vários Estudos Desenvolvidos Em Animais Os Dados Da Inve...unclassified
“…No que diz respeito à atividade antioxidante de N. lappaceum, verificou-se que a respetiva casca tem maior poder antioxidante, em comparação com a semente e a folha, devido ao seu teor de flavonoides e compostos fenólicos, como a geraniina (25).…”
Section: Dos Vários Estudos Desenvolvidos Em Animais Os Dados Da Inve...unclassified
“…Functional foods containing antioxidant bioactive compounds may serve as potential nutritional supplements for the prevention and treatment of chronic diseases. Herein, Tsong and colleagues reviewed the phytochemical compositions and biological activities of Nephelium lappaceum and Nephelium ramboutan-ake , types of tropical fruit from the Sapindaceae family [ 8 ]. Interestingly, phenolics from these two plants served as potential antioxidants that contributed to antiaging, antineoplastic, antimicrobial, and hypoglycemic activities in in vitro and in vivo disease models.…”
Section: Functional Foods As Natural Health-promoting Nutritional Sup...mentioning
confidence: 99%
“…Phytochemicals are classified in accordance with their chemical structure, from simple structures, such as phenolic acids, to highly polymerized structures, such as tannins. These phytochemicals from plants are currently divided into hydroxycinnamic and hydroxybenzoic acid derivatives, flavones, flavonols, flavanols, and anthocyanins ( Tsong et al., 2021 ). Many previous studies reported the phytochemicals of rambutan peel extracts from different regions in the world.…”
Section: Extractions Of Rambutan Peels and Their Phytochemicalsmentioning
confidence: 99%